The SAMI Galaxy Survey: gas streaming and dynamical M/L in rotationally supported systems - Cecil; Fogarty; Richards; Bland-Hawthorn; Lange; Moffett; Catinella; Cortese; Ho; Taylor; Bryant; Allen; et al. (2016)
Line-of-sight velocities of gas and stars can constrain dark matter (DM) within rotationally supported galaxies if they trace circular orbits extensively. Photometric asymmetries may signify non-circular motions, requiring spectra with dense spatial coverage. Our integral-field spectroscopy of 178 galaxies spanned the mass range of the SAMI Galaxy Survey. We derived circular speed curves (CSCs) of gas and stars from non-parametric Diskfit fits out to $r\sim2r_e$. For 12/14 with measured H I profiles, ionized gas and H I maximum velocities agreed. We fitted mass-follows-light models to 163 galaxies by approximating the radial starlight profile as nested, very flattened mass homeoids viewed as a S\'ersic form. Fitting broad-band SEDs to SDSS images gave median stellar mass/light 1.7 assuming a Kroupa IMF vs. 2.6 dynamically. Two-thirds of the dynamical mass/light measures were consistent with star+remnant IMFs. One-fifth required upscaled starlight to fit, hence comparable mass of unobserved baryons and/or DM distributed similarly across the SAMI aperture that came to dominate motions as the starlight CSC declined rapidly. The rest had mass distributed differently from starlight. Subtracting fits of S\'ersic profiles to 13 VIKING Z-band images revealed residual weak bars. Near the bar PA, we assessed m = 2 streaming velocities, and found deviations usually <30 km/s from the CSC; three showed no deviation. Thus, asymmetries rarely influenced our CSCs despite co-located shock-indicating, emission-line flux ratios in more than 2/3.